The lupus family registry and repository (2011)
The Lupus Family Registry and Repository (LFRR) was established with the goal of assembling and distributing materials and data from families with one or more living members diagnosed with SLE, in order to address SLE genetics. In the present article, we describe the problems and solutions of the registry design and biometric data gathering; the protocols implemented to guarantee data quality and protection of participant privacy and consent; and the establishment of a local and international network of collaborators. At the same time, we illustrate how the LFRR has enabled progress in lupus genetics research, answering old scientific questions while laying out new challenges in the elucidation of the biologic mechanisms that underlie disease pathogenesis. Trained staff ascertain SLE cases, unaffected family members and population-based controls, proceeding in compliance with the relevant laws and standards; participant consent and privacy are central to the LFRR's effort. Data, DNA, serum, plasma, peripheral blood and transformed B-cell lines are collected and stored, and subject to strict quality control and safety measures. Coded data and materials derived from the registry are available for approved scientific users. The LFRR has contributed to the discovery of most of the 37 genetic associations now known to contribute to lupus through 104 publications. The LFRR contains 2618 lupus cases from 1954 pedigrees that are being studied by 76 approved users and their collaborators. The registry includes difficult to obtain populations, such as multiplex pedigrees, minority patients and affected males, and constitutes the largest collection of lupus pedigrees in the world. The LFRR is a useful resource for the discovery and characterization of genetic associations in SLE. © The Author 2010. Published by Oxford University Press on behalf of the British Society for Rheumatology. All rights reserved.